2015
DOI: 10.1002/aic.15130
|View full text |Cite
|
Sign up to set email alerts
|

Local hydrodynamic parameters of bubble column reactors operating with non‐Newtonian liquids: Experiments and models development

Abstract: The effects of liquid phase rheology on the local hydrodynamics of bubble column reactors operating with nonNewtonian liquids are investigated. Local bubble properties, including bubble frequency, bubble chord length, and bubble rise velocity, are measured by placing two in-house made optical fiber probes at various locations within a bubble column reactor operating with different non-Newtonian liquids. It was found that the presence of elasticity can noticeably increase the bubble frequency but decreases the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 57 publications
0
18
0
1
Order By: Relevance
“…The physical variables are a function of three physical dimensions ( r = 3), namely, mass (kg), length, (m), and time (t), and then, according to Buckingham's π theorem, we needed to determine π ′ = k − r = 7 − 3 = 4 dimensionless numbers to calculate gas holdup …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The physical variables are a function of three physical dimensions ( r = 3), namely, mass (kg), length, (m), and time (t), and then, according to Buckingham's π theorem, we needed to determine π ′ = k − r = 7 − 3 = 4 dimensionless numbers to calculate gas holdup …”
Section: Resultsmentioning
confidence: 99%
“…The same dimensional analysis used to develop the two‐phase gas holdup correlation (Equation ) was used to develop bubble size and bubble rise velocity correlations for the air–liquid system. The experimental measurements for bubble size and bubble rise velocity obtained by Esmaeili et al for the same liquids as above were used. The authors used a fiber optic probe to perform the measurements.…”
Section: Resultsmentioning
confidence: 99%
“…[ 1 ] To overcome this issue, the multi‐probe method has been used in bubble columns by several authors to measure bubble sizes in various conditions. [ 3–7 ] As pointed out by Chaumat et al, [ 5 ] the method is not adapted to fully heterogeneous regimes, because nearly vertical bubble trajectories are assumed to compute bubble velocities and chord lengths. Another limitation is the difficulty to estimate a Sauter mean diameter from mean bubble chord measurements, because the deconvolution is based on the bubble size distribution, that can hardly be computed without assumptions on its shape (lognormal or else).…”
Section: Introductionmentioning
confidence: 99%
“…Another limitation is the difficulty to estimate a Sauter mean diameter from mean bubble chord measurements, because the deconvolution is based on the bubble size distribution, that can hardly be computed without assumptions on its shape (lognormal or else). Consequently, the few available studies [ 3–7 ] provide very useful results but reported profiles of radial bubble sizes are considered as qualitative.…”
Section: Introductionmentioning
confidence: 99%
“…Fan et al [11] used polystyrene spheres instead of activated sludge to experimentally study the lab-scale oxidation ditch by PDA (particle dynamic analyser) but did not take the activated sludge as non-Newtonian fluid into account [12,13]. For the rheological behavior of a liquid, transparent Newtonian fluids, such as aqueous solution of sodium carboxymethyl cellulose (CMC) or Xanthan solution, always were experimentally used as the liquid phase [14][15][16]. Passos et al [17] additionally used the nonionic surface active agent Triton X-100 to modify the surface tension of the non-Newtonian solutions and found that the diameter of the bubbles decreased.…”
Section: Introductionmentioning
confidence: 99%